Natural based eumelanin nanoparticles functionalization and preliminary evaluation as carrier for gentamicin - De Trizio, Antonella (2017)
Purpose of the work was to modified natural based eumelanin nanoparticles surface by dopamine selfpolymerization (FEUNp), facilitating conjugation through polydopamine bioactive functional groups and improving nanoparticle surface hydrophilicity. SEM, TEM, and AFM characterization confirmed FEUNp spherical shape (230.04 ± 8.25 nm) and their polydopamine coating. Individual indole or indoline structure spectrum at 1600 cm−1 and C:N mass 9.08 was highlighted by FTIR and XPS analysis respectively. Quartzcrystal microbalance with dissipation monitoring (QCM-D) and thermal gravimetric analysis (TGA) showed successful polydopamine adsorption to eumelanin nanoparticles surface, a weight ratio of eumelanin nanoparticles/dopamine of 1/2.46 in the wet state and 1/0.20 in the dry state; the −36.60 ± 0.45 mV negatively surface charges confirms the presence of PD covering. FEUNp were loaded with gentamicin sulfate, for application in infectious diseases therapies, such as osteomyelitis. Nanoparticles drug entrapment efficiency was 32.42 ± 3.21%, and ζ-potential close to neutrality (−1.84 ± 0.58 mV). FEUNp-GS antimicrobial effect was tested on Staphylococcus aureus and Escherichia coli showing gentamicin 24 h sustained release from FEUNp-GS. IC50 and IC90 were 110.60 μg/mL and 216.39 μg/mL against S. aureus, and 54.13 μg/mL and 101.25 μg/mL against E. coli. The results are promising for FEUNp-GS as delivery system potentially useful diverse administration routes.